Monoamine involvement in the antidepressant-like effect induced by P2 blockade - Diniz, Cassiano R.A.F.; Rodrigues, Murilo; Casarotto, Plínio C.; Pereira, Vítor S.; Crestani, Carlos C. [UNESP]; Joca, Sâmia R.L. (Elsevier, 2017)
Depression is a common mental disorder that affects millions of individuals worldwide. Available monoaminergic antidepressants are far from ideal since they show delayed onset of action and are ineffective in approximately 40% of patients, thus indicating the need of new and more effective drugs. ATP signaling through P2 receptors seems to play an important role in neuropathological mechanisms involved in depression, since their pharmacological or genetic inactivation induce antidepressant-like effects in the forced swimming test (FST). However, the mechanisms involved in these effects are not completely understood. The present work investigated monoamine involvement in the antidepressant-like effect induced by non-specific P2 receptor antagonist (PPADS) administration. First, the effects of combining sub-effective doses of PPADS with sub-effective doses of fluoxetine (FLX, selective serotonin reuptake inhibitor) or reboxetine (RBX, selective noradrenaline reuptake inhibitor) were investigated in mice submitted to FST. Significant antidepressant-like effect was observed when subeffective doses of PPADS was combined with subeffective doses of either FLX or RBX, with no significant locomotor changes. Next, the effects of depleting serotonin and noradrenaline levels, by means of PCPA (p-Chlorophenylalanine) or DSP-4 (N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine hydrochloride) pretreatment, respectively, was investigated. Both, PCPA and DSP-4 pretreatment partially attenuated PPADS-induced effects in FST, without inducing relevant locomotor changes. Our results suggest that the antidepressant-like effect of PPADS involves modulation of serotonin and noradrenaline levels in the brain.
Keywords: Antidepressant; ATP; Forced swimming test; Noradrenaline; Serotonin